Blastocyst-like embryo surrogates from stem cells in implantation models. Issue 4 (29th November 2022) - Tian, Siyu; Ruan, Hanzhang; Yeung, William Shu-Biu; Lee, Yin Lau
Abstract : Successful embryo implantation requires highly coordinated maternal-embryo interactions. Implantation failure is a major factor contributing to infertility. However, the mechanism underlying implantation failure remains unclear. An improved understanding of the early implantation process not only improves the success rate of assisted reproductive treatments but also helps in studying the pathophysiology of reproductive disorders. Owing to ethical concerns, in vivo studies of human embryo implantation are not feasible. However, the results obtained from animal models cannot be directly applied to humans. Over the years, in vitro implantation models have been developed to investigate implantation mechanisms. In this review, we discuss the use of different models for generating embryo-like surrogates to study early embryo development and implantation in vitro, with a specific focus on stem cell–derived blastocyst-like embryo surrogates. There is no definitive evidence that the recently established embryo-like models re-capitulate all developmental events of human embryos during the peri-implantation stage. Regardless, stem cell–derived embryo surrogates are the most valuable tools for studying the mechanisms of early cell lineage differentiation and developmental failures during implantation.